Effects of bee bread supplementation on endurance running performance, bone metabolism markers, antioxidant status and selected physiological parameters in athletes - Ping, Fadzel Wong Chee (2015)
INTRODUCTION: Scientific data on the ergogenic effects of bee products consumed at pre exercise and post exercise on sports performance is scanty. PURPOSE: This present study consisted of two phases. The first phase study investigated effects of 8-week bee bread supplementation at pre exercise on endurance running performance, anaerobic power, isokinetic muscular strength and power, antioxidant status and bone metabolism markers in athletes. The second phase study investigated the effects of bee bread supplementation at post exercise, i.e. during recovery on subsequent running performance and physiological parameters in athletes. METHODS: First phase- Twelve male athletes (age: 24.0 ± 1.8 years old; BMI: 22.3 ± 1.3 kg.m-2; VO2max: 52.0 ± 2.8 mL.kg-1.min-1) were recruited in this randomised double blind; placebo-controlled crossover study. Participants consumed either bee bread at a dosage of 20 g.d-1 or placebo for 8 weeks prior to the experimental trial. For the measurement of endurance running performance, participants were required to run at 60% of their respective VO2max on a treadmill for 90 minutes and immediately followed by a 20 minutes running time trial performance on a motorised treadmill. Heart rate, tympanic temperature andrate of perceived exertion (RPE) were recorded at intervals of 10 minutes. Oxygen uptake was measured at intervals of 20 minutes. Blood samples were collected atinterval of 20 minutes during trial to determine plasmaglucose, insulin, lactate, cortisol,free fattyacid, hemoglobin, hematocrit and plasma volume changes. Blood sampleswere also collected at pre supplementation, pre exercise, immediate post exercise and 24hours post exercise to determine total antioxidant status (TAS), reduced and oxidisedglutathione(GSH: GSSG)ratio, F2-Isoprostanesand bone metabolismmarkers (serumtotal calcium, phosphorus, alkaline phosphatase,osteocalcin and C-terminal telopeptide of type 1 collagen (1CTP). Participants’ anaerobic powerand isokinetic muscularstrength and power were measured before andafter 8 weeks of experimental period.Statistical analyses were performed using ANOVA with repeated measures and paired ttest.Second phase-Twelve athletes (age:22.3 ±2.9 years old; BMI: 22.8±2.1kg.m-2; VO2max: 50.0 ±6.4mL.kg-1.min-1) were recruited in this randomised doubleblind;placebo-controlled crossover study. This studywas divided into two stages of recovery.In the first stage of recovery, participants ran at60% of their respective VO2maxon atreadmill for 90 minutes and then rested for 4 hours. During thisfirst recovery period,participants consumed either bee bread at a dosage of 30g.h-1or placebo along withwater equivalent to 150% of body weight loss. Heart rate and tympanic temperaturewere measured at intervals of 20 minutes during the 4 hours recovery. Blood sampleswerecollected at intervals of 30 minutes during the 4 hours recovery to determineplasma glucose, cortisol, insulin, lactate, hemoglobin, hematocrit and plasma volumechanges.Blood sampleswere alsocollectedat pre exercise, immediate post 90 minutesrunning, immediate post 240 minutes recovery, immediate post time trial and 24 hours xxv-Isoprostanes and bone metabolism markers (serum total calcium, phosphorus, alkaline phosphatase, osteocalcin and C-terminal telopeptide of type 1 collagen (1CTP). Participants’ anaerobic power and isokinetic muscular strength and power were measured before and after 8 weeks of experimental period. Statistical analyses were performed using ANOVA with repeated measures and paired t test. CONCLUSION: First phase- Supplementation of bee bread for 8 weeks at a dosage of 20 g daily elicited ergogenic effects on running time trial performance. Second phase- Supplementation of bee bread at a dosage of 30 g.hpower, there were no significant different in mean power, peak power, anaerobiccapacityand anaerobic power between placebo and bee bread trialat preand postsupplementation test. Regarding isokinetic muscular strength and power, isokinetic right kneeextension peak torque and average power at 180o.s-1, and isokinetic right kneeflexion peak torque and average power at 180o.s-1were significantlyhigher at postsupplementation test compared to pre supplementation test in the bee bread trial.Secondphase-In the first stage of 4 hours recovery, distance covered in the beebread trial wassignificantly longer than placebo trial in therunningtime trial performance. Plasmaglucose, insulin and GSH: GSSG ratio was significantlyhigher, whereasF2-Isoprostanewas significantly lower in the bee bread trial incomparison with placebotrial during 4hours recovery. However, heart rate, tympanic temperature, rate of perceived exertion, oxygen uptake, hemoglobin, hematocrit, plasmavolume changes, cortisol, lactate andcreatine kinase in the bee bread trial were not significantly different compared to theplacebo trials. In the second stage of 3 days recovery, there was no significant differencein the distance covered in the bee bread trialcompared tothe placebo trial. Heart rate,tympanic temperature, rateof perceived exertion, oxygen uptake, hemoglobin,hematocrit, plasma volume changes,glucose, lactate, insulin cortisol, total antioxidantstatus, GSH: GSSG ratio and F2-Isoprostane in the bee breadtrial were not significantlydifferent compared to the placebo trial. CONCLUSION:First phase-Supplementationof bee bread for 8 weeks at a dosage of 20 g dailyelicited ergogenic effects on runningtime trial performance.Second phase-Supplementation of bee bread at a dosage of 30g.h-1during 4 hours recovery seems to indicate beneficial effects on subsequentendurance running performance. However, this ergogeniceffect on subsequent xxviiduring 4 hours recovery seems to indicate beneficial effects on subsequent endurance running performance. However, this ergogenic effect on subsequentendurance running performance was not evident following supplementation of bee bread at a dosage of 40 g.day endurance running performance was not evident following supplementation of bee breadat a dosage of 40 g.day-1for 3 days during recovery. xxviiifor 3 days during recovery.